2018
DOI: 10.1161/jaha.116.004782
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Peripheral Vascular Interventions in Select Patients With Lower Extremity Acute Limb Ischemia

Abstract: BackgroundContemporary data on patients presenting with acute limb ischemia (ALI), who are selected for treatment with endovascular peripheral vascular interventions (PVI), are limited. Our study examined outcomes following endovascular PVI in patients with ALI by comparing with patients treated for chronic critical limb ischemia using a regional quality improvement registry.Methods and ResultsOf the 11 035 patients in the Vascular Study Group of New England PVI database (2010–2014), we identified 365 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…PAD is associated with atherosclerosis and is potentiated by other risk factors such as age, smoking, and diabetes. The pathogenesis involving impaired angiogenesis and reduced microcirculation in the skeletal muscle accelerates to intractable limb ischemia in PAD pa-tients (81). Various therapeutic approaches to improve vascularization with angiogenic factors, including vascular endothelial growth factor (VEGF), have shown promising effects in animal models (164) but failed in clinical trials (154).…”
Section: Angiogenesis and Ischemic Revascularizationmentioning
confidence: 99%
“…PAD is associated with atherosclerosis and is potentiated by other risk factors such as age, smoking, and diabetes. The pathogenesis involving impaired angiogenesis and reduced microcirculation in the skeletal muscle accelerates to intractable limb ischemia in PAD pa-tients (81). Various therapeutic approaches to improve vascularization with angiogenic factors, including vascular endothelial growth factor (VEGF), have shown promising effects in animal models (164) but failed in clinical trials (154).…”
Section: Angiogenesis and Ischemic Revascularizationmentioning
confidence: 99%
“…In patients without SARS-CoV-2, amputation rates following acute limb ischemia are between 6% and 23% [36,37]. In this study, the presence of SARS-CoV-2 infection did not influence the amputation-free survival rate: it was only the risk factor for the arterial thrombosis and the trigger for the acute ischemic event.…”
Section: Discussionmentioning
confidence: 48%
“…9 In contrary, analysis by Fagundes et al 12 showed that gender was not a prognostic factor for 30-day amputation in patients treated for ALI. Inagaki et al 23 reported that female sex was independently associated with increased odds of in-hospital adverse events following interventions for ALI, but not specifically increased the risk of limb loss. Several studies have ascertained some other features that increase risk of amputation in patients with ALI that were not seen in our cohort, such as race, age, history of heart failure and malignancy, higher Rutherford class of ischemia, failed previous revascularization procedures, and technical failure of primary interventions.…”
Section: Discussionmentioning
confidence: 99%